Impaired tolerance to the autoantigen LL-37 in acute coronary syndrome - Chernomordik, Fernando; Cercek, Bojan; Zhou, Jianchang; Zhao, Xiaoning; Lio, Nicole Wai Man; Chyu, Kuang-Yuh; Shah, Prediman K.; Dimayuga, Paul C. (Frontiers in Immunology, 2023)
Background LL-37 is the only member of the cathelicidin family of antimicrobial peptides in humans and is an autoantigen in several autoimmune diseases and in acute coronary syndrome (ACS). In this report, we profiled the specific T cell response to the autoimmune self-antigen LL-37 and investigated the factors modulating the response in peripheral blood mononuclear cells (PBMCs) of healthy subjects and ACS patients. Methods and results The activation induced marker (AIM) assay demonstrated differential T cell profiles characterized by the persistence of CD134 and CD137, markers that impair tolerance and promote immune effector and memory response, in ACS compared to Controls. Specifically, CD8+CD69+CD137+ T cells were significantly increased by LL-37 stimulation in ACS PBMCs. T effector cell response to LL-37 were either HLA dependent or independent as determined by blocking with monoclonal antibody to either Class-I HLA or Class-II HLA. Blocking of immune checkpoints PD-1 and CTLA-4 demonstrated the control of self-reactive T cell response to LL-37 was modulated predominantly by CTLA-4. Platelets from healthy controls down-modulated CD8+CD69+CD137+ T cell response to LL-37 in autologous PBMCs. CD8+CD69+CD137+ T cell AIM profile negatively correlated with platelet count in ACS patients. Conclusions Our report demonstrates that the immune response to the autoantigen LL-37 in ACS patients is characterized specifically by CD8+CD69+CD137+ T cell AIM profile with persistent T cell activation and the generation of immunologic memory. The results provide potentially novel insight into mechanistic pathways of antigen-specific immune signaling in ACS.